Rational Emotive Behavior Therapy untuk Mengurangi Kecanduan Game Online - Yadi, Yadi Jatira; Netrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Phenomena among students are related to online game addiction. Namely, students are lazy about working, experience mood changes, and constantly desire to play online games. This research aims to examine the effectiveness of group counseling services with a rational, emotional, behavioral therapy approach to reduce students' online game addiction. The research method used is quantitative with a pre-experimental research type. The experimental design used was one group pre-test and post-test design. The population was 1047 students, and ten students were taken for the sample as the experimental group. Sampling used purposive sampling. The research instrument used a Likert scale model; data was analyzed using the Wilcoxon Signed Rank Test with the help of SPSS version 25.00. The research results showed that the survey of students addicted to online gambling before being given treatment (pre-test) was in the high category, and the survey of students' online gambling addiction after being given treatment was in the low category. Group counseling services with a rational, emotional, behavioral therapy approach effectively reduce students' online gaming addiction. This research shows that rational, emotional, and behavioral therapy with excellent and continuous planning will help group members become more active in thinking and sharing ideas, ideas, and experiences to gain new knowledge and rational thoughts.